Urban Farming Dengan Teknologi Precision Farming Sebagai Upaya Meningkatkan Kesejahteraan Masyarakat dan Pemanfaatan Lahan Kosong - Erna Lovita; Faris Faruqi; Megayani Megayani; Zainal Abidin; Maisa Nur Khoiriyah; Muhammad Ali Dzulfikar (LPMP Imperium, 2024)
Urban Farming is proposed as a solution for unused land (empty land), as well as allowing residents to increase productivity by managing unproductive empty land. The community service program (PKM) is implemented by STIE Indonesia Jakarta in partnership with PT Alif Tekno Farm (ATF). PKM was carried out in Kebon Baru, Tebet, South Jakarta, near the Ciliwung river. The priority of this community service is to empower unemployed individuals or communities while utilizing empty land in urban areas. This program uses precision farming technology with a Smart Nutrition Valve (KNP) tool that saves water, fertilizer, energy and labor. The commodity being developed is a short-lived fruit plant (65 days) which is suitable for lowland areas, namely melons. Training and mentoring is carried out by PT ATF from sowing to harvest. Furthermore, training and assistance in financial management and marketing of harvests was carried out by the STIE Indonesia PKM team. At the end of the program, the target community has independence in managing and developing sustainable urban farming.